O spin doctoring em Portugal : perspectivas de governantes, jornalistas e assessores de comunicação que operam na Assembleia da República - Ribeiro, Vasco (2015)
In the mid-80s the English term "spin doctor" began to being the best way to classify press secretaries that manipulating journalists and, consequently, public opinion (Safire, 1984, October 21; Maltese, 1992; Tankard & Sumpter, 1994; Kurtz, 1998, Manning, 1998; Campbell, 2002). Under this assumption, and with a main objective to try to understand whether there is, in fact, spin doctoring in Portugal, it was decided to conduct elite interviews of the elements who "inhabit" the center of national political activity and the nucleus of higher concentration and productivity political journalism in Portugal - the Portuguese Parliament. Thus, we conducted 30 interviews with the trinomial politics - press secretaries - journalists; namely 1) the press secretaries who carry out their activity for the different parliamentary groups; 2) to correspondent-journalists in Parliament and who deal daily with these professionals; and 3) the politicians who hire their services. It should be stressed among respondents are two former prime-ministers of Portugal, Pedro Santana Lopes and Jose Socrates, and various press advisers and press consultants who served several parties and several governments. Among the results, not only demonstrates the existence of this activity in Portugal, as well as identify its main protagonists.